An Overview on Topical Administration of Carotenoids and Coenzyme Q10 Loaded in Lipid Nanoparticles - Luciana de Souza Guedes; Renata Miliani Martinez; Nádia A. Bou-Chacra; Maria Valéria Robles Velasco; Catarina Rosado; André Rolim Baby (MDPI AG, 2021)
Carotenoids and coenzyme Q10 are naturally occurring antioxidant compounds that are also found in human skin. These bioactive compounds have been the focus of considerable research due to their antioxidant, anti-inflammatory, and photoprotective properties. In this review, the current state of the art in the encapsulation of carotenoids and coenzyme Q10 in lipid nanoparticles to improve their bioavailability, chemical stability, and skin absorption is discussed. Additionally, the main findings are highlighted on the cytotoxic and photoprotective effects of these systems in the skin.